2016
DOI: 10.1016/s1470-2045(15)00365-4
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to access to opioid medicines: a review of national legislation and regulations of 11 central and eastern European countries

Abstract: Control measures designed to prevent the misuse of opioid medicines can often unintentionally restrict legitimate medical use, leaving patients with cancer in pain. This study aimed to develop and validate an assessment instrument based on WHO policy guidelines to systematically identify legal and regulatory barriers to opioid access in 11 European countries (Bulgaria, Cyprus, Estonia, Greece, Hungary, Latvia, Lithuania, Serbia, Slovakia, Slovenia, and Turkey) as part of the Access to Opioid Medication in Euro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
40
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(41 citation statements)
references
References 24 publications
0
40
0
1
Order By: Relevance
“…The lower availability of opioids in Southern and Eastern Europe, as in other areas of the world, can be attributed to several barriers, such as restrictive laws and governmental regulations, fears of possible addiction, lack of adequate training and awareness among healthcare professionals, limited economic resources and restricted formulary availability of opioids (Cherny, Baselga, de Conno, & Radbruch, ; Berterame et al., ; Vranken et al., ; O'Brien et al., ; Vranken et al., ; ESMO (Last accessed October, 5 2018)). Moreover, a recent investigation indicated that gross domestic product and human development index are the strongest determinants of access to opioid analgesics (Berterame et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…The lower availability of opioids in Southern and Eastern Europe, as in other areas of the world, can be attributed to several barriers, such as restrictive laws and governmental regulations, fears of possible addiction, lack of adequate training and awareness among healthcare professionals, limited economic resources and restricted formulary availability of opioids (Cherny, Baselga, de Conno, & Radbruch, ; Berterame et al., ; Vranken et al., ; O'Brien et al., ; Vranken et al., ; ESMO (Last accessed October, 5 2018)). Moreover, a recent investigation indicated that gross domestic product and human development index are the strongest determinants of access to opioid analgesics (Berterame et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…The issue is how to monitor and minimize potential unintended consequences for these patients. The Access to Opioid Medication in Europe (ATOME) project—aimed at the increase of access to opioid medicines in 12 countries with statistical evidence of low opioid consumption‐signaled clearly the importance of sustained investments in public health and education, and improved legal and regulatory systems to ensure safe and appropriate treatment of pain . Perhaps, one of the solutions for both crises lies in better education of health care professionals, patients and policymakers, in parallel with a more balanced view presented in the media.…”
Section: Potential Impact On the Crisis Of Uncontrolled Painmentioning
confidence: 99%
“…Many policies have been developed to address opioid‐related morbidity and mortality . In the United States, states have increasingly implemented prescription drug monitoring programs (PDMPs) and “pill mill” laws .…”
Section: Introductionmentioning
confidence: 99%